Pengaruh Media Tanam Yang Berbeda Terhadap Pertumbuhan Dan Hasil Tanaman Bawang Merah (Allium cepa var. ascalonicum L.) Pada Sistem Hidroponik Substrat - Krisna Gernandus Kuse; Sri Yuniati (Program Studi Agroteknologi Fakultas Pertanian Universitas Dayanu Ikhsanuddin, 2021)
The prospect of shallot (Allium cepa var. ascalonicum L.) cultivation is getting higher considering the increasing market demand every year. However, the limitations and conditions of the land did not allow shallot (Allium cepa var. ascalonicum L.) to grow and produce optimally. One of the efforts to increase the production of shallots (Allium cepa var. ascalonicum L.) on dry land is by using substrate hydroponic cultivation techniques. This research was conducted on Jalan Murhum, Lamangga Sub-district, Murhum District, Baubau City, Southeast Sulawesi Province, taking place from Agust - October 2020. The purpose of this study was to determine the effect of different planting media on the growth and yield of shallot (Allium cepa var. ascalonicum L.) on the substrate hydroponic system. This study used a completely randomized design (CRD) with 6 treatments of growing media namely rice husk charcoal (A), sawdust charcoal (B), coconut fiber powder (C), rice husk charcoal + sawdust charcoal (D), rice husk charcoal + coconut fiber powder (E), and sawdust charcoal + coconut fiber powder (F). Response variables were observed in the form of plant height growth, number of tubers, tuber diameter and plant fresh weight. Furthermore, the observed data were analyzed using analysis of variance followed by the Honest Significant Difference test with a level of 5% on the data that showed a significant effect. Based on the results of observations and analysis, it was concluded that different planting media treatments did not have a significant effect on plant height, tuber number, and tuber diameter but significantly affected the fresh weight of shallot plants in the substrate hydroponic system, but rice husk charcoal + sawdust charcoal (D) planting media gave significant effect on plant fresh weight with an average value of 50 grams per clump.